Financial Performance of PT Perbankan Syariah Indonesia Tbk Before and After the Merger Using the Islamicity Performance Index Approach - Jannah, Raodatul; Sari, Nur Rahmah (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2023)
This study provides a comparison of the performance of BUMN Islamic banking before and after the merger into Bank Syariah Indonesia by analyzing financial ratios using the Islamicity Performance Index approach. This study is a quantitative study with descriptive analysis. This study uses secondary data obtained from the financial reporting data of BUMN Islamic Banking namely Bank Syariah Mandiri, BNI Syariah, and BRI Syariah for the last four years before and after the merger period, starting from 2019-2022. Information about the financial reports of Islamic banks for this study obtained from the news and official websites of each bank. The results of the analysis showed a satisfactory rating with an average value of 1.8. Specifically, to evaluate the value of profit-sharing ratio of Islamic banks before and after the merger into BSI, there is still a shortage of funds distribution using a profit-sharing system, namely mudharabah and musharakah contracts which are basically the main principles of Islamic banking. Then, the value of Zakat Performance Index also shows that the implementation of zakat distribution program in BSI is still not optimal, where the growth of Islamic bank assets or wealth must be proportional to the zakat distributed. As for the value of the Equitable Distribution Ratio, which is the equal distribution of income among stakeholders, starting from the company, employees, and the community is still not optimal. However, the result is different from the performance assessment of Islamic banks through the ratio of Islamicity Income vs. Non-Islamicity Income which shows a very satisfactory result, which means that Bank Syariah Indonesia has achieved success and is operating according to Islamic law. It can be concluded that Islamic banks before and after the merger into BSI have not been able to balance and maximize their business and social performance